Modifikasi Produk Cone Ice Cream Menggunakan Tepung Sorgum Berbasis Daya Terima Konsumen - Nadira Karuniah Putri; Woro Priatini; Ilmiati Tsaniah (Akademi Pariwisata NHI Bandung, 2022)
This study aims to determine the recipe formulation, packaging and labeling, selling price and acceptability of modified ice cream cone products with sorghum flour. This study used an experimental method with a quantitative approach. In this test, the tester made 3 sample recipes, namely cone 1 sample with 100% sorghum flour, cone 2 sample using 70% sorghum flour and 30% tapioca flour, cone 3 sample using 50% sorghum flour and 50% tapioca flour. Furthermore, product sample tests were given to 9 expert panelists for organoleptic tests in order to find the best product and make it a standard recipe. The results of the test selected cone 2 to be the best. Then the sample that has been selected is subjected to a consumer acceptance test of 100 consumer panelists to find out whether the product is accepted by the consumer panelists with a selling price of Rp. 32,000/pack.